1997
DOI: 10.1111/j.1525-1594.1997.tb00350.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical White Blood Cell Damage in Rotary Blood Pumps

Abstract: Mechanical trauma of white blood cells (WBC) due to the operation of a rotary blood pump was examined, using a simple method of trypan blue dye exclusion test for a cell viability measurement. The degree of WBC trauma was investigated using a roller pump (RP) and 3 commercially available centrifugal pumps (Bio-Medicus [BPI, Capiox [CP], Nikkiso [NK]), and compared with the red blood cell (RBC) trauma. Each pump was operated 3 times at a flow rate of 5 Llmin against the total pressure head of 350 mm Hg for 6 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 10 publications
2
18
0
1
Order By: Relevance
“…Because the new pump has no occlusive elements, the alteration of the flow pattern inside the pump due to the action of the membrane could possibly provide an explanation. Concerning changes in the WBC count and despite the fact that the decrease at 3 h ECC was not significant, a clear tendency to decrease was detected (the difference between basal and 1 h post-ECC was significant), which can be explained by the fact that WBC count is highly sensitive to ECC (9,10).…”
Section: Hematological Studymentioning
confidence: 93%
“…Because the new pump has no occlusive elements, the alteration of the flow pattern inside the pump due to the action of the membrane could possibly provide an explanation. Concerning changes in the WBC count and despite the fact that the decrease at 3 h ECC was not significant, a clear tendency to decrease was detected (the difference between basal and 1 h post-ECC was significant), which can be explained by the fact that WBC count is highly sensitive to ECC (9,10).…”
Section: Hematological Studymentioning
confidence: 93%
“…Due to space limitations, this is not considered further in this study. Readers wishing to gain more knowledge on this subject can take a look at for white cells or for platelets.…”
Section: Classification Of Reviewed Hemolysis Modelsmentioning
confidence: 99%
“…This observation matches with observations of white blood cells in a rotary pump that suggest shear-induced damage is an integral effect over time. 26 That is, cell vitality decreases the longer cells are exposed to high shear. Experiments done by Di Carlo et al 27 to examine gene expression in cells exposed to high shear showed no significant changes.…”
Section: Copyright 2012 Author(s) This Article Is Distributed Under mentioning
confidence: 99%